Rapid detection of Streptococcus pyogenes in throat swab specimens by fluorescent in situ hybridization - Tajbakhsh, S.; Gharibi, S.; Zandi, K.; Yaghobi, R.; Asayesh, G. (2011)
Background and Objectives: Streptococcus pyogenes ( S. pyogenes) is an important cause of pharyngitis. Rapid detection of this microorganism in throat specimens is essential to promptly start antibiotic therapy which could be lead to prevent complications and stop transmission of infection to other individuals. In the present study, fluorescent in situ hybridization ( FISH) was compared with culture method for the detection of S. pyogenes in throat swab specimens. Materials and Methods: One hundred eleven patients with pharyngitis were included in this study. The throat swab specimens of these patients were investigated by both conventional culturing and FISH. Results: Based on the results of this investigation, the sensitivity and specificity of FISH were 88.9 and 97.8, respectively. Strikingly, in the specimen of one patient who had received antibiotic previous to clinical sampling, S. pyogenes was detected by means of FISH, whereas the culture method could not detect this bacterium. Conclusions: It seems that FISH is a suitable method for quick identification of S. pyogenes in throat swab specimens. When FISH is positive, culturing is not necessary. But because of the limited sensitivity of FISH for detection of S. pyogenes in throat swab specimens, culturing shoud be performed if FISH was negative.